2018
DOI: 10.1080/15459624.2018.1479064
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of total inward leakage measured using sodium chloride (NaCl) and corn oil aerosol methods for air-purifying respirators

Abstract: The International Organization for Standardization (ISO) standard 16900–1:2014 specifies the use of sodium chloride (NaCl) and corn oil aerosols, and sulfur hexafluoride gas for measuring total inward leakage (TIL). However, a comparison of TIL between different agents is lacking. The objective of this study was to measure and compare TIL for respirators using corn oil and NaCl aerosols. TIL was measured with 10 subjects donning two models of filtering facepiece respirators (FFRs) including FFP1, N95, P100, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…Moreover, not only the droplet size but also the enhanced ionic nature of the bio-aerosol, induced by NaCl wetting, may lead to easier capture /better filtration by filter material. It was shown that a fine NaCl bio-aerosol penetrates less deep in face mask material (FFP1 and N95) as compared with corn oil bio-aerosol [ 35 ]. CE-standard criteria for professional face masks ask filter capacities based on testing with plain paraffin aerosol: as surfactants highly change paraffin aerosol properties [ 36 ], this may not fully estimate the behaviour of viral-loaded bio-aerosols consisting of enveloped virus or surfactant (phospholipid) vesicles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, not only the droplet size but also the enhanced ionic nature of the bio-aerosol, induced by NaCl wetting, may lead to easier capture /better filtration by filter material. It was shown that a fine NaCl bio-aerosol penetrates less deep in face mask material (FFP1 and N95) as compared with corn oil bio-aerosol [ 35 ]. CE-standard criteria for professional face masks ask filter capacities based on testing with plain paraffin aerosol: as surfactants highly change paraffin aerosol properties [ 36 ], this may not fully estimate the behaviour of viral-loaded bio-aerosols consisting of enveloped virus or surfactant (phospholipid) vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…Charge shielding of mucin or mucin-like macromolecules that consequently undergo gelation, stabilizing ALF/air interface and reducing its breakup, resulting in a reduced tendency of the ALF to disintegrate into very small droplets Saline droplets (emulsion) [31] Mechanistic study of NaCl droplets ± surfactant Added to nanoemulsions, NaCl makes finer micellar droplets "aggregate", making the droplet size distribution to move to a bigger size range (so will lead to faster deposition), while surfactant in contrast breaks up the droplets to smaller sizes Saline phospholipid droplets [32] Mechanistic study of effect of NaCl on phospholipid vesicles and bilayers -Na + and Cl − binds with the lipid head and induces strong hydrophobic repulsion on the lipid tail -This leads to enhanced hydrophobic repulsion on lipids and so forces lipids to attach firmly on the surface substrate Much larger external energy is needed for vesicle formation in salt solutions than in pure water Sodium chloride aerosol [35] Mechanistic study of NaCl and corn oil (bio)aerosol on filtration by face mask materials (FFP1, N95, P100, and elastomeric half-mask respirators)…”
Section: Mechanistic (Physicochemical) Effects and In Vitro Studiesmentioning
confidence: 99%
“…Studies have assessed a range of parameters, including the FFR’s particle filtration efficiency, material strength, and “fit”. The latter quantifies how tight the seal between the respirator and the wearer’s face is, being generally derived from the ratio of non-toxic sodium chloride particles generated by the testing equipment present in the ambient air to that within the respirator on the wearer [ 86 ] (compared with a self-administered “fit check” prior to use, to determine if the FFR seals properly to the wearer’s face prior to use [ 87 ]).…”
Section: Impact Of Disinfection On Ffrsmentioning
confidence: 99%
“…The filtration efficiencies of these masks to protect against non-infectious agents have been investigated thoroughly. The wide variation in filtration efficiency as a function of fabric material used was already demonstrated by Shakya et al (2017) and Rengasamy et al, 2010 , Rengasamy et al, 2018 who studied the filtration efficiency using diesel particles (<2.5 μm) and NaCl particles (<1 μm) respectively.…”
Section: Cloth Masks Are They Protective?mentioning
confidence: 73%